2021
DOI: 10.1111/jce.15038
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical basis behind the neuromodulation effects associated with pulmonary vein isolation

Abstract: The anatomical basis underlying the neuromodulation effects seen with pulmonary vein (PV) isolation (PVI) is not fully understood. Left atrial (LA) electro‐anatomical maps of 38 patients who underwent catheter cardioneuroablation for vagally mediated bradycarrhythmias were studied. During the procedure, LA ganglionic plexi (GPs) were systematically identified and ablated. Design PVI lines were created on these maps by a blinded observer, and the degree of overlap between four GPs and individual PVs was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…We have recently demonstrated that different GP sites demonstrate different neuromodulation characteristics during radiofrequency application. 25 While ablation around the left-sided GPs causes a VR (Videos S2 and S3), ablation of the superior right atrial GP increases heart rate acutely without any VR (Video 4). Furthermore, we demonstrated that right side first strategy may cause an attenuation of VR ablation around the left-sided GPs, 26 and hence our preference for starting from the left-sided GPs.…”
Section: Procedural Steps Of Electrogram-guided Ganglionated Plexus M...mentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that different GP sites demonstrate different neuromodulation characteristics during radiofrequency application. 25 While ablation around the left-sided GPs causes a VR (Videos S2 and S3), ablation of the superior right atrial GP increases heart rate acutely without any VR (Video 4). Furthermore, we demonstrated that right side first strategy may cause an attenuation of VR ablation around the left-sided GPs, 26 and hence our preference for starting from the left-sided GPs.…”
Section: Procedural Steps Of Electrogram-guided Ganglionated Plexus M...mentioning
confidence: 99%
“…Otherwise, we perform empirical ablation around the posteroseptal wall of the superior vena cava for the superior right atrial GP site (Video S). We have recently demonstrated that different GP sites demonstrate different neuromodulation characteristics during radiofrequency application 25 . While ablation around the left‐sided GPs causes a VR (Videos S and S), ablation of the superior right atrial GP increases heart rate acutely without any VR (Video ).…”
Section: How To Perform Cardioneuroablationmentioning
confidence: 99%
“…Otherwise, we perform empirical ablation around the posteroseptal wall of the superior vena cava for the superior right atrial GP site (Video 1). We have recently demonstrated that different GP sites demonstrate different neuromodulation characteristics during radiofrequency application (25). While ablation around the left-sided GPs causes a VR (Video 2 and 3), ablation of the superior right atrial GP increases heart rate acutely without any VR (Video 4).…”
Section: Procedural Steps Of Electrogram-guided Ganglionated Plexus M...mentioning
confidence: 99%
“…Intrinsic cardiac ANS is organized in a network of ganglionated plexi (GP), which are accommodated in EAT, mainly around PVs [81].…”
Section: Epicardial Adipose Tissue (Eat) and Autonomic Nervous System (Ans)mentioning
confidence: 99%